A flash-based on-the-job training game. (1st January 2013) - Werneck, Eduardo; Chang, Maiga
Most of research results show that the educational games are good to increase student's learning motivation in formal learning. This research reveals the project of designing and implementing a web-based educational game within a real corporate environment. It is amazing to find that what a real world company looks for is such a small and simple game. The game has been approved by the officer and used to provide to phone and face-to-face sales who have no minimum necessary knowledge of selling watercrafts insurance and have interest in using game-based learning mode instead of traditional PowerPoint presentation mode. The results show that the game mode's dispersion is quite high, showing a more volatile situation. Good news is, although the employees did not like the game itself, they are still willing to try the game, instead of the presentation, if offered.